EVALUASI PELAKSANAAN PENILAIAN PEMBELAJARAN GEOGRAFI SMA DI KABUPATEN BANTUL - Muhammad Nursa'ban (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: An Evaluation of the Implementation of the Geography LearningAssessment in Senior High Schools in Bantul Regency. This study aims toevaluate the implementation of geography assessment in senior high schools basedon the Regulation by the Minister of the National Education Number 20 Year 2007about the National Standard of Assessment. This study was an evaluation studyemploying the Stakes model. The sample, selected by means of the simple randomsampling technique, consisted of 56 geography teachers in Years X, XI, and XII ofsenior high schools. The data were collected using a questionnaire and observationguide and analyzed using the descriptive analysis based on the predeterminedcriteria. The findings are as follows. 1) The antecedent phase, consisting ofassessment principles, is in the very good category. 2) The transaction phase,consisting of assessment techniques, is in the good category. The instruments,mechanisms, and processes of assessment are in the very good category. 3) Theoutcome phase shows that the assessment of geography learning is in the very goodcategory.Keywords: assessment, geography learning